Communities for Environmental Protection: Fostering Responsibility and Sustainability - Mina, Risno; Fality, Firmansyah; Miranda, Miranda; Imani, Rizka Amelia (Universitas Internasional Batam, 2024)
Community participation in environmental protection is increasingly crucial in facing global environmental challenges. This article outlines the essence of community participation and its responsibilities in providing protection for the environment, from the individual to the community level. It emphasizes the importance of community awareness, knowledge, and concrete action to achieve sustainable development. The research method used is normative or doctrinal research. Normative research methods are legal research methods that involve reading documents related to the problem to be researched. This research method refers to legal standards and principles contained in statutory regulations. The essence of community participation in environmental protection is increasing community awareness and taking active action to preserve the environment, including increasing awareness, independence, empowerment, cooperation, ability and leadership, supervision, and local culture. Community responsibility in providing protection for the environment involves various very important aspects. society's primary responsibilities in terms of understanding and awareness, reduction of ecological footprint, participation in sustainable development, reporting and monitoring, education and extension, and participation in environmental movements. Community responsibility in environmental protection is implemented in the form of concrete actions.